تربية الأطفال في نظرية المعرفة في القرآن الكريم - Ujang Saefullah; Ahmad Zaidi; Dede Suparman (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
This study aims to explore the instructions of the Qur’an on epistimologi education of children. Based on the idea that childhood is a phase of life that is very important and influential on subsequent periods. Educational success in childhood will have a positive impact on the personality and life of the child in the future. As well as failure. This study is the library research with a qualitative approach. The primary data sources are the Qur’an and Tafsir. While the secondary data sources are books related to the theme of research. The research results showed that the Qur’an very concerned about the education of children and encourage parents and teachers to carry out such a comprehensive education. According to the Qur’an children can be jewelry of the world (zînat al-hayât al-dunyâ), a gem that boast (qurrata a’yun), trial for parents (fitnah), and enemies ('aduww). Several things related and affect a child's education is the goal, materials, methods and educator. Everything has to be integrated in an integrated manner for all the requirements are met properly.